WUJUD VARIASI BAHASA YANG TERDAPAT PADA TUTURAN KONTEN KREATOR TIKTOK TAUFIK RAGIL:KAJIAN SOSIOLINGUISTIK - Fatimiyah Ratu Izzahroh; Aisyah Aisyah; Azer Ilham (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Language variations are a form of the use of different languages based on speakers. Factors that influence speakers of the occurence of language variations can come from social status factors, individuals, culture,. This paper discusses the form of language variations inthe speech of a TikTok creator content. TikTok is a social media application that allows users to make and upload videos. TikTok Taufik Ragil’s creator content is one of the creator content originating from Madura. The use of the style language used by Taufik Ragil is his trademark, so that without seeing it and just hearing it of course for someone who often watching the content will find out. The data obtained uses descriptive qualitative research methods, data is taken from severalvideo content of Taufik Ragil and uses the Records of the Records. In this analysis it can be concluded that Taufik Ragil uses a form of language variation in terms of speakers.